Pendidikan Multikultural: Membangun Harmonisasi dan Kerukunan Melalui Penguatan Nilai Toleransi Di Desa Mojorejo Kota Batu Jawa Timur - Taufikurrahman, Taufikurrahman; Fajrin, Megawati; Ali Efendi, M Sabilal; Riswan, Mokhamad (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2022)
Religious tolerance is evidenced by the unification of society through togetherness. This indicates that the religious phenomenon that exists as a reality in the midst of society gets a positive response so it is interesting to study. Meanwhile, on the other hand, the discourse of strengthening the harmonization of plural society which is manifested in the attitude of religious tolerance, was born and proclaimed by various parties. Mojorejo Village, Batu City managed to get appreciation from the Batu City government in the form of giving an award as "Village of Awareness of Religious Community Harmony and Village of Peace". This success is a proud achievement, considering that the heterogeneous typology of the people in Mojorejo village is quite high. Methodologically, this research uses a qualitative approach with the type of case study. Data collection techniques in this study include: interviews. observation and documentation through the media, archival records. Data Validity Test Extended observations, Increases persistence, and Triangulation The results and conclusions are the ideological dimensions, the values ​​of Islamic religious teachings, Taswasut, Tasamuh, Ta'adul, the values ​​of Buddhist teachings, love of metta, sympathy mudita, balanced mind upekkha, values ​​of Christian teachings, love, patience, responsibility. ideological dimensions: the value of Islamic religious teachings taswasut, tasamuh, ta'adul, the value of Buddhist teachings of love metta, sympathy mudita, balanced mind upekkha, Christian religious values ​​of love, patience, responsibility, dimensions of knowledge, tolerance, awareness, togetherness, mutual cooperation. dimensions of experience, interfaith prayer together, village salvation, village clean, dance studio. dimensions of consequences/effects, agro-agricultural economics which accommodates and buys and sells farmers' income, social work together to build villages, clean villages, religious friendship between communities, takziah, interfaith prayer together, village salvation. politics (honest, fair, clean and transparent. dance studio culture